Pengembangan Budidaya Jamur Desa Wargaluyu, Kecamatan Tanjungmedar, Kabupaten Sumedang - Dedi Supriadi (UNISBA Press, 2024)
Abstract. The low number of jobs in the countryside has resulted in high unemployment and depopulation from rural to urban areas in order to increase unemployment rate and depopulation from rural to urban areas with the aim of improving standard of living. In order to overcome these problems, LLDikti through the Thematic KKN program held Program (KKN) Thematic held Gotong Royong Membangun Desa (GRMD) service activities, one of which is the Village (GRMD), one of whose programs is One Village One Product (OVOP). The activity This service activity aims to explore and develop regional superior products in Wargaluyu Village, Tanjungmedar District, Sumedang Regency through oyster mushroom cultivation in order to reduce poverty levels and expand employment opportunities. in order to reduce poverty levels and expand employment opportunities. The collection of data collection was carried out through observations and interviews based on SWOT analysis, namely analysis of the internal environment consisting of strengths (Strengths) and weaknesses (Strengths). analysis of the internal environment consisting of strengths and weaknesses and the external environment consisting of opportunities. external environment consisting of opportunities (Opportunities) and threats (Threats). The results of The results of this analysis show that it is necessary to hold a socialization of mushroom cultivation in the form of training, production and marketing management, and entrepreneurship. The result of this service is the formation of economic independence in Wargaluyu village through an oyster mushroom business in the form of baglog making, production and marketing management, and entrepreneurship. oyster mushroom business in the form of baglog making, mushroom cultivation and various processed oyster mushrooms. Abstrak. Rendahnya jumlah lapangan pekerjaan di pedesaan mengakibatkan tingginya angka pengangguran dan adanya depopulasi dari pedesaan ke perkotaan dengan tujuan meningkatkan taraf kesejahteraan hidup. Guna mengatasi masalah tersebut, LLDikti melalui program Kuliah Kerja Nyata (KKN) Tematik mengadakan kegiatan pengabdian Gotong Royong Membangun Desa (GRMD) yang salah satu programnya adalah one village one product (OVOP). Kegiatan pengabdian ini bertujuan untuk mengeksplorasi dan mengembangkan produk unggulan daerah di Desa Wargaluyu Kecamatan Tanjungmedar Kabupten Sumedang melalui budidaya jamur tiram dalam rangka mengurangi tingkat kemiskinan dan memperluas lapangan pekerjaan. Pengumpulan data dilakukan melalui observasi dan wawancara berdasarkan analisis SWOT yaitu analisis lingkungan internal yang terdiri dari kekuatan (Strengths) dan kelemahan (Weaknesses) serta lingkungan eksternal yang terdiri dari peluang (Opportunity) dan ancaman (Threats). Hasil analisis tersebut menunjukkan bahwa perlu diadakan sosialisasi mengenai budidaya jamur berupa: pelatihan sumber daya, manajemen produksi dan pemasaran, serta kewirausahaan. Hasil dari pengabdian ini adalah terbentuknya kemandirian ekonomi di desa Wargaluyu melalui usaha jamur tiram berupa pembuatan baglog, budidaya jamur dan aneka olahan jamur tiram.